Information Society: A Fundamental Concept or a Trendy Keyword - Žilinskaitė-Vytienė, Viktorija; Čiupailaitė, Dalia; Kirtiklis, Kęstas (Sociologija. Mintis ir veiksmas, 2017)
This article is a metatheoretical research of the foundations of information society studies. The research focuses on the most cited articles on the topic of information society from sociology and communication studies, published in the international Web of Science database. After analysing the methods by which information society is conceptualised, the contexts of where this keyword appears and the functions that it performs, the authors conclude that the most important debate in the field is neither theoretical or methodological, but rather normative – i.e., between the enthusiasts of information society as progressive social development and its adversaries – the exponents of critical theory. This leads to a conclusion that information society studies rather embody trends of political and public discourse than scholarly interests.